EFEKTIFITAS DEWAN KOMISARIS INDEPENDEN DALAM MENGURANGI MANAJEMEN LABA - Andayani, SE., M.Si., Ak, Tutut Dwi; SE., M.Si, Muhammad Yusuf (STIE Muhammadiyah Pekalonga, 2011)
The purpose of this study is to analyze the effective of independent directors in lowering earnings management. The effective of independent director measured by the proportion of independent director and ordinance I-A compliance. The object of this research is manufacturer companies listed in the Indonesian Stock Exchange.This empirical research used secondary data based on purposive sampling technique. The samples consist of 33 firms, collected from 1999 until 2007, with total samples 297 samples. The 1999-2007 annuals report used as main data available in company website and BEI (www.idx.co.id). Hypothesis tests used multiplied analysis regression and paired sample test.The result of the hypothesis test indicates that proportion of independent directors had significantly negative effect on earnings management. This study also found that there is difference in the average practice of earnings management before and after the ordinance I-A year 2000 on independent directors. The next research to be suggested to try other variable which possible have an effect on to earnings management as audit committee and others.Keywords: earnings management, independent of directors, ordinance